An inherent strain based multiscale modeling framework for simulating part-scale residual deformation for direct metal laser sintering - Chen, Qian; Liang, Xuan; Hayduke, Devlin; Liu, Jikai; Cheng, Lin; Oskin, Jason; Whitmore, Ryan; To, Albert C. (Additive manufacturing, 2019)
Residual distortion is a major technical challenge for laser powder bed fusion (LPBF) additive manufacturing (AM), since excessive distortion can cause build failure, cracks and loss in structural integrity. However, residual distortion can hardly be avoided due to the rapid heating and cooling inherent in this AM process. Thus, fast and accurate distortion prediction is an effective way to ensure manufacturability and build quality. This paper proposes a multiscale process modeling framework for efficiently and accurately simulating residual distortion and stress at the part-scale for the direct metal laser sintering (DMLS) process. In this framework, inherent strains are extracted from detailed process simulation of micro-scale model based on the recently proposed modified inherent strain model. The micro-scale detailed process simulation employs the actual parameters of the DMLS process such as laser power, velocity, and scanning path. Uniform but anisotropic strains are then applied to the part in a layer-by-layer fashion in a quasi-static equilibrium finite element analysis, in order to predict residual distortion/stress for the entire AM build. Using this approach, the total computational time can be significantly reduced from potentially days or weeks to a few hours for part-scale prediction. Effectiveness of this proposed framework is demonstrated by simulating a double cantilever beam and a canonical part with varying wall thicknesses and comparing with experimental measurements which show very good agreement.